Cardiomyopathy in COVID-19 Survivors: Mechanism, Management, and Prevention - Renan Sukmawan (Jurnal Kardiologi Indonesia, 2020)
Coronavirus disease (COVID-19) caused by infection of SARS-CoV-2 as of April 2020 has been confirmed in more than 2.3 million people, with more than 150 thousands deaths across the globe. It has been known that COVID-19 patients with underlying cardiovascular diseases and its risks including: hypertension, diabetes, coronary artery disease, and cerebrovascular diseases may develop more severe respiratory track symptoms requiring intensive care. Some patients may presenting with myocarditis or acute cardiomyopathy, which has high mortality and morbidity. There was also evidence of myocardial Injury with an increase of troponin in one-third of those infected by covid-19. It is conceivable that among those who recover from COVID-19 infection, there is a risk of developing further cardiomypathy once the pandemic receding in the future. It is important to pay attention to this survivor group since the pandemic may be lasting for longer period. Optimal medical treatment and comprehensive prevention should be taken to manage those high risk patients of developing cardiomyopathy during hospital care as well post discharge. These includes provide best available COVID-19 drugs, cardiovascular medications, and social preventive measures.